1991
DOI: 10.1111/j.1439-0507.1991.tb00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia pachyderznatis: properties and storage

Abstract: Summary. Five strains of Malassezia pachydermatis isolated from small animals in Bratislava were subcultured, maintained under sterile paraffin oil and preserved in liquid nitrogen. Morphological and physiological characteristics as well as the analysis of long chain fatty acids of the cell mass were determined. The results showed that the maintenance in liquid nitrogen is the most satisfactory method of preservation of pure cultures of Malassezia pachydermatis. Zusammenfassung. Fünf Stämme der Art Ma‐lassez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Cells survive lyophilization [2,51]. Preservation in liquid nitrogen is also efficient [51,52]. Lorenzini & de Bernardis [53] suggested the use of the glucose nutrient agar supplemented with 1·5% yeast extract and 1% Tween 80; cultures maintained at room temperature were kept alive for at least 3 months.…”
Section: Mycologymentioning
confidence: 78%
See 1 more Smart Citation
“…Cells survive lyophilization [2,51]. Preservation in liquid nitrogen is also efficient [51,52]. Lorenzini & de Bernardis [53] suggested the use of the glucose nutrient agar supplemented with 1·5% yeast extract and 1% Tween 80; cultures maintained at room temperature were kept alive for at least 3 months.…”
Section: Mycologymentioning
confidence: 78%
“…Numerous protein bands ranging from 15·0–145·7 kDa were detected, but profiles did vary according to the origin of the strains (external ear canal or skin). Breierova et al [52] demonstrated that the content of unsaturated acids (oleic, linoleic, myristoleic and palmitoleic) was 2·5–7·5 times greater than that of saturated acids (palmitic, stearic and myristic). Great variations were noticed between strains.…”
Section: Mycologymentioning
confidence: 99%
“…As in other yeasts, the cytoplasmic microtubules, spindle and astral microtubules are probably involved in positioning, migration and division of the nucleus (Banuett and Herskowitz, 2002). Migration of the nucleus to the bud before mitosis, also observed at the ultrastructural level, gives support to inclusion of the Malassezia genus into the fungal group basidiomycota Breierová et al, 1991;Guillot et al, 1995;Guého et al, 1996). The distribution of microtubules during the cell cycle of M. pachydermatis was found to be similar to that in other basidiomycetous yeasts (Slaninová et al, 1999;Kopecká et al, 2001b;Banuett and Herskowitz, 2002;Straube et al, 2003).…”
Section: Distribution Of Microtubules and Nuclear Position In M Pachmentioning
confidence: 64%